Bridging Indigenous Knowledge and Science: How Ethnoecology Proyeks Enhance Students’ Environmental Literacy - Fadilah, Nurul Akmal; Ramdhan, Billyardi; Suhendar (Universitas Muhammadiyah Pontianak, 2025)
This study aims to examine the effect of ethnoecology project-based learning on students' environmental literacy in ecosystem-related materials. This study used a quasi-experimental design with a pretest-posttest control group. The sample consisted of 41 seventh-grade students from junior high schools in Sukabumi Regency, including 22 students in the experimental group and 19 students in the control group. The data collected were quantitative, obtained through environmental literacy tests, attitude scale questionnaires, and student response questionnaires. The test instruments measured environmental literacy indicators used were knowledge, competence, disposition, and environmentally responsible behavior. Data were analyzed using an independent t-test through SPSS software. The results showed that the average N-Gain in the experimental class was 0.60 (medium category), higher than the control class, which was 0.33. The t-test results showed a significance level of p = 0.000 (p < 0.05), which indicated a significant difference between the two groups. The affective aspect also experienced an increase, indicated by the average score of student attitudes and behaviors being in the